A multi-pole magnetorheological clutch powered by permanent magnets and excitation coils. (January 2023) - Wu, Jie; Deng, Bingbing; Huang, Yuming; Zhang, Hui; Tang, Shaoyu
This article presents a new design of a multi-pole magnetorheological (MR) clutch, with a hybrid magnetization using several permanent magnets and several excitation coils. The permanent magnets are used as the first source of generating the magnetic field, and the excitation coils are used to adjust the magnetic field to the required value. Firstly, a detailed illustration of the mechanical design of the MR clutch is presented. The principal design parameters of the proposed clutch are determined to achieve maximum torque according to the magnetic circuit. After that, the torque model is established, and simulations are conducted to evaluate the magnetic circuit design. Subsequently, an experimental set-up is established, and the proposed MR clutch is designed and manufactured, and a series of experiments are carried out. The results clearly show that different torque output can be obtained by controlling the current magnitude and direction of each coil. Finally, to achieve a precise feedback torque control, the design of a current controller is carried out using conventional proportional-integral-derivative (PID) control scheme. The results demonstrate that the designed PID controller can be used to obtain the desired torque.